2022
DOI: 10.3389/fnmol.2022.856262
|View full text |Cite
|
Sign up to set email alerts
|

WNK3 kinase maintains neuronal excitability by reducing inwardly rectifying K+ conductance in layer V pyramidal neurons of mouse medial prefrontal cortex

Abstract: The with-no-lysine (WNK) family of serine-threonine kinases and its downstream kinases of STE20/SPS1-related proline/alanine-rich kinase (SPAK) and oxidative stress-responsive kinase-1 (OSR1) may regulate intracellular Cl− homeostasis through phosphorylation of cation-Cl− co-transporters. WNK3 is expressed in fetal and postnatal brains, and its expression level increases during development. Its roles in neurons, however, remain uncertain. Using WNK3 knockout (KO) mice, we investigated the role of WNK3 in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…It remains unclear how blocking KCC2 from DIV2 to DIV8 can alter membrane properties of neurons two weeks later. Our study adds to an increasing number of studies that demonstrate that intracellular chloride levels can modify ion channels, and therefore membrane excitability, in often unpredictable ways (Huang et al, 2012; Seja et al, 2012; Goutierre et al, 2019; Sinha et al, 2022). Most notably, it was shown that membrane levels of specific potassium channels are regulated via KCC2 (Goutierre et al, 2019) and the chloride-dependent kinase WNK3 (Sinha et al, 2022), and it will be important to further examine the role of various chloride channels in membrane excitability (Jentsch, 2016; Jentsch and Pusch, 2018; Akita and Fukuda, 2020).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It remains unclear how blocking KCC2 from DIV2 to DIV8 can alter membrane properties of neurons two weeks later. Our study adds to an increasing number of studies that demonstrate that intracellular chloride levels can modify ion channels, and therefore membrane excitability, in often unpredictable ways (Huang et al, 2012; Seja et al, 2012; Goutierre et al, 2019; Sinha et al, 2022). Most notably, it was shown that membrane levels of specific potassium channels are regulated via KCC2 (Goutierre et al, 2019) and the chloride-dependent kinase WNK3 (Sinha et al, 2022), and it will be important to further examine the role of various chloride channels in membrane excitability (Jentsch, 2016; Jentsch and Pusch, 2018; Akita and Fukuda, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Our study adds to an increasing number of studies that demonstrate that intracellular chloride levels can modify ion channels, and therefore membrane excitability, in often unpredictable ways (Huang et al, 2012; Seja et al, 2012; Goutierre et al, 2019; Sinha et al, 2022). Most notably, it was shown that membrane levels of specific potassium channels are regulated via KCC2 (Goutierre et al, 2019) and the chloride-dependent kinase WNK3 (Sinha et al, 2022), and it will be important to further examine the role of various chloride channels in membrane excitability (Jentsch, 2016; Jentsch and Pusch, 2018; Akita and Fukuda, 2020). Interestingly, effects seem to strongly depend on cell type (Seja et al, 2012) and timing of the chloride manipulation (Lim et al, 2021; Sinha et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the mechanism seems different as mIPSC frequency and synapse numbers were not affected in VU-treated slices (Peerboom et al, 2023). In interpreting our results and that of previous studies, it is hard to disentangle the versatile pharmacological profile of furosemide and the many roles for neuronal chloride in regulating cell volume (Jentsch and Pusch, 2018) and possibly cellular excitability (Huang et al, 2012; Seja et al, 2012; Jentsch and Pusch, 2018; Goutierre et al, 2019; Sinha et al, 2022; Peerboom et al, 2023). Our study further underscores the need for a beter understanding of the role of chloride as an intracellular messenger in developing neurons.…”
Section: Discussionmentioning
confidence: 59%
“…Our results suggest that one week treatment with furosemide indirectly affect ac�vity-induced swelling of neurons, but the mechanism remains unresolved. In interpre�ng our results and that of previous studies, it is hard to disentangle the versa�le pharmacological profile of furosemide and the many roles for neuronal chloride in regula�ng cell volume (Jentsch and Pusch, 2018) and possibly cellular excitability (Huang et al, 2012;Seja et al, 2012;Jentsch and Pusch, 2018;Gou�erre et al, 2019;Sinha et al, 2022;Peerboom et al, 2023).…”
Section: Possible Effect Of Furosemide On Cell Volume Regulationmentioning
confidence: 62%